High content analysis of cellular localisation and biocompatibility of CdTe and CdSe / ZnS nanoparticles - Williams, Yvonne (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2010)
The rules governing particle properties at the nanoscale relate more to the laws of quantum mechanics than classical mechanics. Biologists have been keen to harness nanoparticles not only for these properties but also because there are now numerous engineered particles similar in size to those occurring naturally in the environment. The potential in vivo benefits of nanoparticles have been explored including delivery of site-specific drugs and specific cell killing, which have long been the holy grail of cancer therapy. Nanoparticles may also have a role in fundamental research as robust reagents in bioimaging, although in vivo applications have been beset with problems of stability and toxicology. The use of fluorescent probes in tracking molecules within cells has been a valuable tool in biology. However conventional probes are prone to bleaching, interfere with cell physiology, and have different absorption bands thus making multiplexing an expensive and complicated procedure. The development of semiconductor nanocrystals or quantum dots (QD) is proving to be an exciting new concept for biolabelling. Useful QD properties include photostability, broad absorption bands and size dependent emission wavelengths.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin